(untitled) (Research, Society and Development, 2022)
Glanders is an infectious disease caused by the bacterium Burkholderia mallei that mainly affects equines, without treatment or vaccine. It is a zoonosis of economic relevance, with few scientific publications on its occurrence in several Brazilian states. Thus, the present work aims to analyze the spatial distribution of glanders in the state of Tocantins from the geoprocessing of the outbreaks, as well as the evolution of the disease from the first case, reported in 2015, to the year 2021. The data were obtained from the Agência de Defesa Agropecuária do Tocantins (ADAPEC), and the coordinates of the focus properties were used to produce thematic maps, using the QGIS program, which allowed the evaluation of the spatial distribution of the disease in the years studied. The program was used to prepare the herd distribution map by municipality, organized in a scale system. In the analyzed period, 37 foci and 91 cases of glanders were registered, being 74.73% cases in the equine species, 21.98% in mules and 3.3% in donkeys distributed in a non-uniform way from Tocantins. There is a higher frequency of notifications in the north and southwest of the state, making it possible to highlight strategic points for intensifying prevention and control actions with the use of georeferencing.